Comparative Theology After Liberalism - Nicholson, Hugh (Modern theology, 2007)
This article first identifies two reasons for the current marginality of the theological sub-discipline of "comparative theology." The first is an awareness of the imperialistic character of the universalist (inclusivist and pluralist) theologies of the recent past. The second is the assumption that Christianity's relations with other religious are extrinsic to Christian identity. Drawing on Kathryn Tanner's critique of postliberalism, it argues that interreligious comparison is integral to a theology that recognizes the essentially relational nature of Christian identity. This recognition implies a continuous revision of Christian identity that checks the tendency to essentialize and thereby exclude religious "others."